How much do we spend on prescription medicines?: Out-of-pocket costs for patients in Australia and other OECD countries - Kemp, A.; Preen, D.; Glover, J.; Semmens, James; Roughead, E. (CSIRO Publishing, 2011)
Objectives: To determine changes in out-of-pocket expenditure on prescription medicines for Australian patients, and how patient expenditure compares with other Organisation for Economic Co-operation and Development (OECD) countries. Methods: We examined out-of-pocket expenditure on prescription medicines by patients in Australia between 1970 and 2007, and between Australia and 15 other OECD countries (Canada, Czech Republic, Denmark, Finland, France, Germany, Japan, Republic of Korea (South Korea), Luxembourg, Poland, Slovak Republic, Spain, Sweden, Switzerland and the United States) in 2005. Findings: Spending on publicly subsidised medicines by Australian patients increased from $16 per person in 1971 to $62 in 2007. Patient expenditure on all prescription medicines had risen to $134 per person in 2007. Out-of-pocket expenditure for Australian patients ranked 4th of 14 OCED countries with universal pharmaceutical subsidies. Australian patients pay 28% of national pharmaceutical expenditure; more than patients in South Korea (27%), Slovak Republic (26%), Sweden (22%), France, Luxembourg, Japan and Switzerland (17%), Germany (15%), Czech Republic (11%) and Spain (6%), but less than patients in Finland (36%), Denmark (33%) and Poland (34%). Conclusions: Compared to other OECD countries, Australian out-of-pocket costs are now in the mid to upper range. Further increases have the potential to significantly affect access to care.